Solomon Islands : Fourth Review Under the Extended Credit Facility Arrangement. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2015)
KEY ISSUES Recent Developments and Outlook. Solomon Islands held its parliamentary elections on November 19, 2014 and elected a new government led by Prime Minister Manasseh Sogavare, representing the Democratic Coalition for Change. The country's Gold Ridge mine, its only gold mine, remains closed and the chances of it re-opening are limited given current gold prices. At the same time, the logging industry is being adversely affected by the depletion of forestry resources. As a result, the near-term outlook has worsened. While lower oil prices constitute a windfall to consumers and producers, diversifying sources of growth and boosting the competitiveness of the economy are key to strengthening medium-term growth prospects. The risks to the outlook are to the downside. Program Performance. Performance under the Extended Credit Facility (ECF) arrangement has been broadly satisfactory. Performance criteria for end-June 2014 were met by large margins. Indicative targets (ITs) for end September 2014 were also met, except for those on health and education spending, which were both narrowly missed in June and September 2014. Despite delays, the authorities have made progress in implementing the structural reform agenda. Policy Recommendations ? In the medium term, recalibrate ambitious spending plans in line with implementation capacity, revenue envelope, financing availability, and the need to preserve fiscal buffers for resilience against shocks given the serious setback in mining prospects linked to the closure of the only gold mine. ? Strengthen the quality of public spending and fiscal management by advancing Public Financial Management (PFM) reform, including improving the transparency and accountability in the use of constituency funds. ? Maintain the current monetary stance but stand ready to tighten policy if credit growth and inflationary pressures surge. ? Strengthen financial regulation and supervision, including supervision of the National Provident Fund, and improve private sector access to credit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet